Experimental analysis of the performance of new TCP extensions over hybrid satellite networks - Banzon, Peter Antonio B. (2001)
This study looks into how new Transmission Control Protocol (TCP) extensions perform on top of a hybrid satellite network. Two network topologies, namely a hybrid satellite network and a terrestrial WAN are studied with three different TCP implementations, namely, TCP Reno, TCP SACK and TCP FACK. For both network topologies, data are obtained by actual measurements of file transfers over an operational network. The first network is composed of the Asian Internet Interconnection Iniatives (AI3) Project's satellite-based network test bed as well as various other networks to which the Advanced Science Technology Institute (ASTI) is connected. The second network implements a terrestrial Wide Area Network (WAN) setup for comparison. Analysis of results shows that both TCP SACK and TCP FACK outperforms TCP Reno for large file transfers. For relatively small transfers, the three TCP implementations have the same performance. Furthermore, TCP SACK significantly outperforms TCP FACK for small file transfers while TCP FACK outperforms TCP SACK for very large file transfers. Overall, TCP SACK is the recommended stack for general purpose applications. Actual traffic patterns by users of both networks highlight the importance of enhancing the slow start phase of TCP in order to improve the performance of TCP as perceived by actual users.